Fully physically crosslinked organohydrogel with ultrastretchability, transparency, freezing-tolerant, self-healing, and adhesion properties for strain sensor. (22nd February 2023) - Ji, Feng; Zeng, Yingying; Yu, Qingyu; Zhu, Junqiu; Xu, Jing; Guo, Jiangbin; Zhou, Qiliang; Luo, Shuiyuan; Li, Junjie
Abstract: Recently, conductive hydrogels have gained great attention in intelligent wearable devices, but the simultaneous realization of stretchability, transparency, anti-freezing, self-healing, and adhesion properties by an easy method is still a big challenge. Herein, a novel multifunctional organohydrogel based on noncovalent intermolecular interactions was developed by simply polymerization hydroxyethyl acrylamide (HEAA) in LiCl cryoprotectant/water (Cryo/water) solution via one-pot photo-polymerization method. Hydrogen bonding interactions of PHEAA-PHEAA and PHEAA-Cryo were the main driving force for gel formation. The LiCl and cryoprotectant gave PHEAA-Cryo-LiCl organohydrogel good conductivity and anti-freezing properties, respectively. The effects of the gel composition on the mechanical, transparency, anti-freezing, and conductivity properties of PHEAA-Cryo-LiCl organohydrogels were researched in detail. Moreover, poly(hydroxyethyl acrylamide)-glycerin-lithium chloride (PHEAA-Gl-LiCl) organohydrogel displayed good self-healing and adhesion properties owing to the reversible hydrogen bonding. Based on PHEAA-Gl-LiCl organohydrogel, a strain sensor was prepared for detecting human movements within a wide temperature range (−40 °C–25 °C), and the result showed various human motions could be detected stably, including joint movement, making a fist, swallowing or pronouncing, suggesting the potential application for the next generation of intelligent wearable sensors. Graphical abstract: Image 1 Highlights: The fully physically crosslinked PHEAA-Cryo-LiCl organohydrogel was successfully constructed by a simple one-pot method. The PHEAA-Cryo-LiCl organohydrogel displays excellent stretchability, optical transparency, and anti-freezing properties. The PHEAA-Gl-LiCl organohydrogel had good self-healing and adhesion properties to diverse substrates. The PHEAA-Gl-LiCl organohydrogel-based strain sensor could stably detect various human motions in a wide temperature.